Zaćma u chorego z atopowym zapaleniem skóry – opis przypadku i przegląd piśmiennictwa - Strzałka, Anna; Przepiórkowski, Ryszard (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Atopic cataract is one of several kinds of presenile cataracts, which develops in 20% of patients suffering from atopic dermatitis. Atopic cataract is the most frequently bilateral and characterized by fast progression. This type of cataract creates more and more important social problem, because of the young age of patients, who are usually professionally active and increasing incidence of atopic dermatitis in population. The aim of this paper is to present the case report of the atopic cataract in patient who was operated in the Regional Ophthalmologic Hospital in Krakow, and the review of the literature.